Trishna Based on the Novel "Tess of the D'Urbervilles" by Thomas Hardy - Winterbottom, Michael; Zyskind, Marcel; Pinto, Freida; Ahmed, Rizman; Seth, Roshan (Artificial Eye, 2012)
Almost any great story possesses two qualities that define it as a classic; those are timelessness and universality. Michael Winterbottom renews the relevance of classic Victorian novel "Tess of the D’Urbervilles" by transplanting its heroine into modern day India and renaming her Trishna, who is played with remarkable grace by Freida Pinto. The pertinent issues of a bygone time receive new light in this retelling and prove they still matter in contemporary society. Questions of elitism, female subjugation, and moral hypocrisy take on new meaning here. Certainly, Trishna’s powerful storytelling and unique thematic resonance make it a film that can stand on its own legs, but its real genius is revealed in how cleverly the filmmakers have adapted it. [www.soundonsight.org]